PERTANGGUNGJAWABAN PIDANA TERHADAP GELANDANGAN DAN PENGEMIS (GEPENG) DITINJAU DARI PERSPEKTIF HAM (STUDI KASUS PENGADILAN NEGERI SINGARAJA) - Adi Prasetya Atmaja, Ketut; Yusa Darmadi, A.A.Ngurah; Walesa Putra, I Made (Kertha Wicara : Journal Ilmu Hukum; Vol. 02, No. 02, April 2013)
Vagrants and beggars or often called gepeng is a classic problems that must be addressed by the government in order to maintain public order. The one way the government act is the regulation of Buleleng regency with Buleleng Local Regulation No. 6 Year 2009 regarding Public Order containing provisions to criminalize the gepeng. Meanwhile gepeng is part of the poor people that must be protected and preserved as they have human rights set forth in the Constitution of Republik of Indonesia Year 1945.
Keywords: Criminal Responsibility, Gepeng, Human Rights, Buleleng Regency.